Effects of urbanization on spatial demography change in Ibeju-Lekki, Lagos peri-urban settlement. Issue 3 (27th May 2018) - Adedire, Funmilayo Mokunfayo; Adegbile, Michael B. O.
Abstract: Peripheral settlements in Lagos are undergoing spatial and demographic transformation that is not captured by conventional regional planning. Ibeju-Lekki, a peri-urban settlement in Lagos State with vast land area, has grown phenomenally due to rapid urbanization. This article examines the change in spatial demography in Ibeju-Lekki. Data were collected through primary and secondary sources including observation, structured questionnaires, archived land use maps (1980–2002), and satellite images (2006 and 2016). Three-hundred seventy questionnaires were administered to household heads in purposively selected 16 settlements in the study area. Quantitative data were analyzed using descriptive statistics while qualitative data were subjected to satellite image analysis. Findings show a spatial expansion predominantly for residential land use, aggravated by the housing deficit in Lagos metropolis and aided by improved transport linkages. The study recommends a reclassification of Lagos peri-urban settlements based on change in spatial demography to accommodate improved infrastructure and sustainable development.